How to experimentally monitor the fatigue behaviour of vibrating mechanical systems? - Cianetti, Filippo (Strojniški vestnik, 2020)
Fatigue damage and, in general, fatigue behaviour is not simple to observe or estimate during the operational life of a generic vibrating mechanical system. There are a lot of theoretical or numerical methods that allow to evaluate it or by knowing a priori the loading conditions and obtaining output stress states by adopting numerical models of the mechanical system or by directly experimentally measuring and acquiring stress/strain states. A few examples of instruments (e.g. rain flow recorders) or measurement chains dedicated to estimate it in time domain or frequency domain are found in the literature but none that fully both observes the system dynamic behaviour and estimates the related actualized cumulated damage, and, thus, none that can estimate the residual life of the system itself. In this paper, a simple time-domain method, designed to monitor the instantaneous fatigue behaviour by definition of the instantaneous and cumulated potential damage or of equivalent damage signal amplitude is presented, based on rain-flow counting method and a damage linear cumulation law and starting from system dynamics signals. This methodology was designed to overestimate real damage to alert the system manager before any crack starts and to be simply translated into electronic boards that can be mounted on generic mechanical systems and linked to one of the sensors that usually monitor system functionality.
Keywords: damage; fatigue; metoda štetja rainflow; naključne obremenitve; poškodbe; rain flow counting; random loads; regulacijski sistemi; utrujanje; vibracije